IMPLEMENTASI PROGRAM KOKURIKULER SPELLING BEE COMPETITION SEBAGAI PENUNJANG PEMBELAJARAN BAHASA INGGRIS - Fajri, Ahmad; Dewi, Ratna Sari; Nurhasanah, Ana; Setiawan, Sigit (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
This research aims to describe the planning of the Spelling Bee Competition co-curricular program as a support for English language learning, describe the implementation of the Spelling Bee Competition co-curricular program as a support for English language learning and explain the evaluation of the Spelling Bee Competition co-curricular program as a support for English language learning. This research uses a qualitative approach with descriptive methods. The results of the research show that the planning of the Spelling Bee Competition co-curricular program as a support for English language learning consists of several stages, namely, the stage of reaching out to the future to estimate future conditions and needs (needs analysis), determining the goals to be achieved, determining the policies to be pursued regarding the goals. previously determined, determine a program, estimate the costs required, determine the schedule and work procedures to be followed. The process of implementing the Spelling Bee Competition co-curricular program as a support for English language learning focuses more on the process of determining the form of activity, then preparing the steps for implementing the activity and fulfilling the principles of organizing co-curricular activities. Evaluation of the Spelling Bee Competition co-curricular program as a support for English learning includes activity results, advantages and disadvantages of activities and follow-up activities.